How Belief System as The Best Driver of Control in Increasing Performance - Yudi Yudi; Yvonne Augustine (Universitas Pasundan, 2024)
Based on the essence of contingency theory and resource-based view, this research focuses on examining the influence of the management control system (MCS) on the performance of Indonesian public health sector organizations from both financial and non-financial perspectives such as sustainability practices mediated by organizational learning. The research technique used in this study included distributing questionnaires to 172 respondents from health service facilities in 22 provinces in Indonesia. The outcome of this study showed that there was a significant positive impact of MCS elements and organizational learning to organizational performance except for the diagnostic control system. Organizational learning mediates belief system on organizational performance. The conclusion of this study is expected to benefit the health practitioners and regulators aimed at promoting effectiveness of MCS practices on the performance of public sector organizations, especially belief systems as the best driver of control in increasing performance. The originality of this research is a study that investigates the complete elements of the MCS on the performance of public health sector organizations from both financial and non-financial perspectives such as sustainability practices, in addition to using organizational learning capabilities as mediation.